A Novel Initialization Technique for Decadal Climate Predictions - Volpi, Danila; Meccia, Virna L.; Guemas, Virginie; Ortega, Pablo; Bilbao, Roberto; Doblas-Reyes, Francisco J.; Amaral, Arthur; Echevarria, Pablo; Mahmood, Rashed; Corti, Susanna (Frontiers in Climate, 2021)
Model initialisation is a matter of transferring the observed information available at the start of a forecast to the model. An optimal initialisation is generally recognized to be able to improve climate predictions up to a few years ahead. However, systematic errors in models make the initialisation process challenging. When the observed information is transferred to the model at the initialisation time, the discrepancy between the observed and model mean climate causes the drift of the prediction towards the model biased attractor. Although such drifts can be generally accounted for with a-posteriori bias correction techniques, the bias evolving along the prediction might affect the variability that we aim at predicting, and disentangling the small magnitude of the climate signal from the initial drift to be removed represents a challenge. In this study, we present an innovative initialisation technique which aims at reducing the initial drift by performing a quantile matching between the observed state at the initialisation time and the model state distribution. The adjusted initial state belongs to the model attractor and the observed variability amplitude is scaled towards the model one. Multi-annual climate predictions integrated for 5 years and run with the EC-Earth3 Global Coupled Model have been initialised with this novel methodology and their prediction skill has been compared with the non-initialised historical simulations from CMIP6 and with the same decadal prediction system but based on full field initialisation. We perform a skill assessment of the surface temperature, the heat content in the ocean upper layers, the sea level pressure and the barotropic ocean circulation. The added value of the quantile matching initialisation is shown in the North Atlantic subpolar region and over the North Pacific surface temperature as well as for the ocean heat content up to 5 years. Improvements are also found in the predictive skill of the Atlantic Meridional Overturning Circulation and the barotropic stream function in the Labrador Sea throughout the 5 forecast years when compared to the full field method.